Results of endoscopic management of anastomotic biliary strictures after orthotopic liver transplantation - Sinan AKAY,; Zeki KARASU,; Galip ERSÖZ,; Murat KILIÇ,; Murat AKYILDIZ,; Fulya GÜNŞAR,; Ulus AKARCA,; Yücel BATUR,; Tankut İLTER, (Turkish Journal of Gastroenterology, 2019)
-